KEKERASAN RUMAH TANGGA TERHADAP WANITA: KAJIAN PERBANDINGAN SOSIO-PERUNDANGAN DI MALAYSIA DAN INDONESIA - Hanafi Arief; Rohani Abdul Rahim (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
In the present era of pursuing a developed country, family life becomes very challenging and this raised pressure on livelihood needs that are not easily predictable. This causes married couples to face many problems including in having mutual understanding, respect and protection. As a result almost every year, there has been an increase of domestic violence (DV) cases, which was conducted by husbands onto wives. Theoretically, DV victims are controlled, suppressed and abused physically, psychologically and economically because of their weaker position, whom are considered inferior compared to the perpetrator that are more superior. The meaning of